Alveolar Mandible Osteoplasty with Combined Bone Transplants - N. E. Selsky; A. V. Trokhalin; D. M. Mukhamadiev (Креативная хирургия и онкология)
Introduction. There are various osteoplasty methods aimed at managing the challenge of jaw atrophy. When the scope of the osteoplasty is extensive it is not always possible to prepare an appropriate amount of bone tissue without additional surgeries. In some cases there is a lack of intraoral bone tissue sources for this kind of operations. Using extraoral sources of bone tissue is not always justified; it is invasive and patients take longer to recover and return to work. Using alternative sources of bone biomaterials might help establish a less invasive osteoplasty protocol.Goal. To demonstrate the efficiency of alveolar ridge osteoplasty with the application of laminar technique and using various combinations of autograft and allograft tissues.Materials and methods. To achieve the goal set we have examined and treated fourteen patients (N=14) surgically. All patients presented a clinical picture of severe atrophy in dentoalveolar segments 3 and 4, knife-edged ridge, Cawood and Howell class IV–V. Depending on the combination of autograft and allograft biomaterials patients were split into three study groups and one control group.Results and discussion. Positive outcomes for the treatment administered were observed in 13 out of 14 patients. Complications were determined by the lack of soft tissue, exposure of the graft or its suppuration. All the patients in all the groups underwent a control CT which confirmed the bone tissue growth at the area of the augmentation performed.Conclusion. Using the bone biomaterial allograft in combination with autograft bone makes it possible to get good clinical results in all the groups observed. This method may be a method of choice eliminating the additional invasive procedure of bone transplant harvesting; it does, however, require further, more detailed research.